The innovative technologists and formation of the technical operation system of civil aircraft avionics - Kuznetsov Sergey (MATEC Web of Conferences, 2021)
The system of technical operation (TO) of on-board equipment or avionics of aircraft (AC) as an object of research is a set of objects and means of technical operation, maintenance and repair programs, as well as personnel performing procedures and organizing the processes of TO. The quality of the TO system is manifested in the TO process - a set of processes of intended use, operational control, maintenance, restoration and repair. The TO process, as a process of changing the TO states, can be considered as a controlled random process, determined on the set of operation states by probabilistic characteristics. The quality of the TO system is characterized by a set of properties that determine its ability to satisfy with the maximum economic efficiency the needs of the TO system of the aircraft, while ensuring the required levels of reliability and readiness of the avionics for operation. That is, the TO system has all the features inherent in complex technical systems - a hierarchical ramified structure, subordination of goals and restrictions, wide interrelationships in the process of functioning. The main research apparatus in solving problems of optimization of processes and synthesis of TO systems is the apparatus of the theory of mathematical modeling of complex technical systems, based on a system approach, the integration of analytical and simulation modeling. The article solves the problem of determining the values of the parameters of the TO system such that the costs of the system during the TO process reach a minimum when all the required tasks are completed and all restrictions on the system’s own parameters and indicators of its technical efficiency are met.